Interleukin-33-Dependent Accumulation of Regulatory T Cells Mediates Pulmonary Epithelial Regeneration During Acute Respiratory Distress Syndrome - Tan, Wen; Zhang, Bohan; Liu, Xinpei; Zhang, Chaoji; Liu, Jianzhou; Miao, Qi (Frontiers in Immunology, 2021)
Acute respiratory distress syndrome (ARDS) triggered mostly by infection, is a syndrome that involves respiratory failure. ARDS induces strong local infiltration of regulatory T cells (Treg cells) in the lungs, and Treg cells were recently highlighted as being related to the repair of various tissue. However, at present, there is still a lack of adequate evidence showing the impact of Treg cells on pulmonary regeneration during ARDS. Here, we verified that Treg cells are strongly induced in ARDS mice and Treg depletion results in impaired lung repair. Moreover, Treg cells show high expression of ST2, a cellular receptor for the tissue alarmin IL-33, which is strongly upregulated in the lung during ARDS. In addition, we demonstrated that IL-33 signaling is crucial for Treg cell accumulation, and ST2-blocked mice show a decrease in the Treg cell population. Critically, transfer of exogenous IL-33 into Treg depleted mice restored Treg cells and facilitated lung regeneration by promoting alveolar type II cell (AEC2) recovery in ARDS, with elevated neutrophils infiltration and upregulated TGF-β1 release. These results emphasized the importance of IL-33 in accelerating the expansion of pulmonary Treg cells and promoting their activity to mediate pulmonary epithelial regeneration during ARDS in a TGF-β1-dependent manner.